Does self-modulated learning vs. algorithm-regulated learning of dermatology morphology affect learning efficiency of medical students? - Danya Traboulsi; Jori Hardin; Laurie Parsons; Jason Waechter (Canadian Medical Education Journal, 2019)
Background: Deliberate practice is an important method of skill acquisition and is under-utilized in dermatology training. We delivered a dermatologic morphology training module with immediate feedback for first year medical students. Our goal was to determine whether there are differences in accuracy and learning efficiency between self-regulated and algorithm-regulated groups.